Complete mitochondrial genome of copperband butterflyfish Chelmon rostratus (Teleostei, Perciformes, Chaetodontidae). (3rd May 2016) - Wang, Li-Juan; You, Feng; Wu, Zhi-Hao
Abstract: In this study, the complete mitochondrial (mt) genome of the copperband butterflyfish Chelmon rostratus from Beibu Bay, China, was determined. It is one of the most common coral reef fish in South China Sea. The total length of C. rostratus mitogenome is 16, 538 bp, which consists of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and a control region, with the genome organization and gene order being identical to other typical vertebrate mitogenomes. The overall nucleotide composition of the H-strand is 28.05% A, 28.94% T, 16.22% G and 26.79% C, with an A + T bias. This study will provide the first complete mitochondrial genome of Chelmon rostratus as useful information for the application of fish phylogenetic relationship analysis within the butterflyfish species.